Hubungan Perilaku Personal Hygiene Saat Menstruasi dengan Kejadian Pruritus Vulvae pada Remaja Putri di Pondok Pesantren Putri Daruzzahra Arrifa’i Kelurahan Merjosari Kecamatan Lowokwaru Kota Malang - Ummah, Wiqodatul; Utami, Woro Tri (NHM PRESS, 2023)
Background: The development and maturation of the reproductive organs occurs during adolescence. It was during this period that there were many disturbances, especially during menstruation, the emergence of itching in the vulva area and vaginal opening was often experienced by most adolescents, in this case it is known as Pruritus Vulvae. Objective: To determine the relationship between Personal Hygiene Behavior during Menstruation and Pruritus Vulvae Incidence in Young Women. Method: This research with cross sectional approach. The population in this study were young women at the Putri Daruzzahra Arrifa'i Islamic Boarding School, Merjosari Village, Lowokwaru District, Malang City. The sample of this research were 32 teenagers. How to take samples using total sampling technique. Data collection used primary data through a google form questionnaire, and analysis in this study used the chi-square test. Result: The results of the analysis showed that there were 21 (65.6%) respondents in the good personal hygiene behavior category, and 12 (37.5%) respondents experienced pruritus. The statistical test analysis using the chi square test obtained P value of 0.000 (<0.005) which can concluded that there is a relationship between Personal Hygiene Behavior During Menstruation and Pruritus Vulvae Incidence in Young Girls at Daruzzahra Arrifa'i Islamic Boarding School, Merjosari Village, Lowokwaru District, Malang City. Conclusion: There is a relationship between Personal Hygiene Behavior During Menstruation and the Incidence of Pruritus Vulvae in Young Girls at Daruzzahra Arrifa'i Islamic Boarding School, Merjosari Village, Lowokwaru District, Malang City.